2018
DOI: 10.1039/c8cp05301d
|View full text |Cite
|
Sign up to set email alerts
|

Crosslinked PVA/SSA proton exchange membranes: correlation between physiochemical properties and free volume determined by positron annihilation spectroscopy

Abstract: At low humidity (<30 RH%), water molecules begin to fill the intermolecular spaces in the membrane. At high humidity (80 RH%) the membrane swells; the free volume size increases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(114 citation statements)
references
References 50 publications
2
83
0
Order By: Relevance
“…This is due mainly to the loss of moisture adhesion and removal of water molecules from the polymer matrix, with the pristine PVA incurring the greatest loss of water molecules. The second stage of weight loss for the pristine PVA is then observed from 250 to 300 °C, which is attributable to the breakage of C-C and C-O bonds, as the thermal energy is then able to degrade the linear chains of the pristine PVA (Gomaa et al 2018). The ester linkages and additional hydrogen bonds present within the cross-linked PVA structures are gradually degraded in the range of 160 °C.…”
Section: Thermal Stabilitymentioning
confidence: 99%
“…This is due mainly to the loss of moisture adhesion and removal of water molecules from the polymer matrix, with the pristine PVA incurring the greatest loss of water molecules. The second stage of weight loss for the pristine PVA is then observed from 250 to 300 °C, which is attributable to the breakage of C-C and C-O bonds, as the thermal energy is then able to degrade the linear chains of the pristine PVA (Gomaa et al 2018). The ester linkages and additional hydrogen bonds present within the cross-linked PVA structures are gradually degraded in the range of 160 °C.…”
Section: Thermal Stabilitymentioning
confidence: 99%
“…Gomaa et al 25,26 prepared cross-linked polyvinyl alcohol/ sulfosuccinic acid (PVA/SSA) as a proton exchange membrane for fuel cell applications. They found that the ionic conductivity and the thermal stability of the crosslinked membranes improved by increasing the concentration of SSA.…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies reported a similar trend of lower resistivity at higher temperatures and related this decrease to the re-agglomeration of carbon black aggregates to be responsible for the observed decline in the resistivity [62,63]. Additionally, the increase of the free volume size inside the polymers due to the temperature rise has been shown to increase the conductivity, which is another possible explanation for the observed decrease in resistivity [64].…”
Section: Temperature Dependence Of Volume Resistivitymentioning
confidence: 76%